Comprehensive Study of the Potential and Suitability of PLTS as a Renewable Energy Solution in Pelawi Utara Village - Rahmaniar -; Agus Junaidi; Rizky Syahputra; Alfonsus Sinamo (LKP KARYA PRIMA KURSUS, 2024)
This comprehensive study examines the potential and suitability of implementing Solar Power Plant (PLTS) as a renewable energy solution in Pelawi Utara Village. The study used a quantitative approach through primary data collection in the form of community energy demand surveys and solar energy potential measurements, as well as secondary data from relevant agencies. Potential analysis showed that the research location has an average solar radiation of 4.8 kWh/m²/day with an effective irradiation duration of 5 hours per day, while the community's electrical energy needs reach an average of 900 kWh per month with a peak load of 35,094 kW. The technical feasibility study indicated that the implementation of a 45,000 kW solar power plant could meet 30% of the community's total energy demand. The economic analysis showed investment feasibility with a payback period of 8 years, Net Present Value (NPV) of IDR 165,000,000,000, and Internal Rate of Return (IRR) of 15%. The results of this comprehensive study conclude that PLTS is an appropriate renewable energy solution for Pelawi Utara Village based on resource potential, technical aspects, and economic feasibility.